Investment in next generation networks and the role of regulation: a real option approach - Gavosto, Andrea (2010)
The current regulatory debate in the telecommunications industry in Europe and elsewhere is dominated by the issue of if and how to regulate next generation networks (NGN) which operators plan to roll out in the near future. The crucial issue is whether an extension of current regulatory obligations onto future networks would hamper the investment by large European operators. The paper applies a real option model to explain the investment decision in next generation networks. One important result of the model is that regulation affects the investment decision only in the initial period when uncertainty is still very high. The real option model has been calibrated with parameters drawn from real data for a new entrant and from educated estimates for an established operator. Four different regulatory regimes and their impact on the timing of the investments have been simulated: a temporary regulatory holiday is shown to be an effective regulatory tool in order to induce immediate investments.